Effectiveness of hermetic bag storage technology to preserve physical quality attributes of shea nuts. (March 2023) - Obeng-Akrofi, George; Maier, Dirk E.; White, Wendy S.; Akowuah, Joseph O.; Bartosik, Ricardo; Cardoso, Leandro
Abstract: Shea nuts are a nutritionally and economically important tree crop harvested seasonally in rural areas of sub-Saharan Africa. Storage losses are a major constraint in the shea nut value chain, with substantial amounts lost prior to processing and marketing. Hermetic bags have proven to be a viable technology for the effective storage of grains, oilseeds and pulses in sub-Saharan Africa due to their efficacy, low cost, and commercial availability. However, hermetic bag storage technology has not been investigated for the preservation of shea nut quality. In this study, shea nut storage in hermetic bags was compared to storage in jute sacks and woven polypropylene (PP) bags. Shea nuts had an initial moisture content of 7.3% (w.b.) and insect damage of 28%. Each storage treatment consisted of 12 bags of 20 kg shea nuts with samples taken from 3 bags every 6 weeks over a 30-week storage period. As ambient temperature and relative humidity conditions varied over time, moisture content varied within 1 percentage point in hermetic bags compared to 3 percentage points in the jute sacks and PP bags. Insect damage was maintained below 30% in hermetic bags, compared to 80% and 82% in PP bags and jute sacks, respectively. Weight loss due to insect damage was 4.5% in the hermetic bags compared to 10.1% and 11.6% in the jute sacks and PP bags, respectively. Carbon dioxide concentration in the hermetic bags remained below 6% over 30 weeks, indicating low insect and microbial activity. The results of this study have proven hermetic bag storage technology to be a viable option for the quality preservation of dry shea nuts, which should be strongly considered for adoption in the shea nut value chain. Highlights: The effectiveness of hermetic bag storage technology was assessed for storage of shea nuts. Storage of shea nuts was done over 30 weeks, and physical quality attributes were monitored. Hermetic bag storage technology proved effective for maintaining physical quality attributes of shea nuts. Hermetic bag storage technology is strongly recommended for adoption in the shea nut value chain.